2021
DOI: 10.3389/fphar.2021.760768
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Anti-infective Potential of Thymol Against Early Childhood Caries Causing Dual Species Candida albicans and Streptococcus mutans

Abstract: Early childhood caries (ECC), a severe form of caries due to cross-kingdom interaction of Candida albicans and Streptococcus mutans, is a serious childhood dental disease that affects majority of the children with poor background. The present study investigated the anti-infective potential of thymol against C. albicans and S. mutans dual species for the management of ECC. Thymol, a plant derivative of the monoterpene group, has been well known for its numerous biological activities. Thymol at 300 μg/ml concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
1
16
0
1
Order By: Relevance
“…Moreover, thymol showed a dose-dependent reduction in acidogenesis of Str. mutans and reduced the expression of multiple virulence-associated genes, including the gtfB gene also investigated in this study (Priya et al, 2021). Because these results are reminiscent of the data presented here, this supports our hypothesis that thymol is one of the main active components of the O. vulgare ethanolic extract.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, thymol showed a dose-dependent reduction in acidogenesis of Str. mutans and reduced the expression of multiple virulence-associated genes, including the gtfB gene also investigated in this study (Priya et al, 2021). Because these results are reminiscent of the data presented here, this supports our hypothesis that thymol is one of the main active components of the O. vulgare ethanolic extract.…”
Section: Discussionsupporting
confidence: 91%
“…The only virulence-associated gene under study that was not significantly affected by extract treatment was an enterococcal gelatinase (gelE), which has been implicated in the degradation of dentin (Lee and Tan, 2015). Although some studies have reported that other bioactive compounds can influence Gtf activity, acidogenesis and expression of the selected virulenceassociated genes in cariogenic bacteria, this is the first report that describes those effects for an O. vulgare extract (Furiga et al, 2008;Lee and Tan, 2015;Khan et al, 2016;Shafiei et al, 2020;Priya et al, 2021;Reis et al, 2021). Especially against the backdrop of an antimicrobial resistance crisis, anti-virulence properties are believed to be more robust to the development of resistance and provide an attractive complementation to the more conventionally studied bacteriostatic and bactericidal activities (Dickey et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…Thymol significantly reduced the biofilm formation and virulence of both S. mutans and C. albicans, including acidogenicity (acid production from the dietary carbohydrates), acidurity (able to survive under lethal pH condition), and yeast-to-hyphal transition, in single- and mixed-species biofilm communities. Notably, these microorganisms did not show resistance against thymol, which could be associated with the fact that this compound showed regulatory effects on many genes/transcriptional regulators of both organisms ( Priya et al, 2021b ). The synergistic interaction between S. mutans and C. albicans within the carious biofilm leads to enhanced virulence of both pathogens.…”
Section: Thymolmentioning
confidence: 99%
“…The synergistic interaction between S. mutans and C. albicans within the carious biofilm leads to enhanced virulence of both pathogens. Recent investigations have demonstrated that the presence of C. albicans supports the extensive colonization of S. mutans in the dental biofilm ( Waltimo et al, 2000 ; Priya et al, 2021b ). Thus, thymol, due to its ability to inhibit fungal filamentation and morphogenesis, and impair S. mutans acidogenic and aciduric ability, could be a practical candidate for the prevention and treatment of early childhood caries; however, more confirmatory investigations are required.…”
Section: Thymolmentioning
confidence: 99%
“…Polyphenol extracts from green tea or cranberries have also been shown to effectively inhibit the acidogenicity and metabolic activity of C. albicans-S. mutans biofilms, decrease EPS and microbial biovolumes, and disrupt biofilm structure (59,60). Thymol, the major constituent of thyme essential oil, is another nature product that showed ability to diminish the C. albicans-S. mutans dual-species biofilm formation and virulence (61). In addition, thymol was found to be effective in diminishing C. albicans-S. mutans dual-species virulence in the invertebrate model Galleria mellonella (61).…”
Section: Approaches To Disrupt C Albicans-s Mutans Biofilmmentioning
confidence: 99%